Transmission Line Model for an Edge-Coupled Patch Antenna - Wiset Saksiri; Mitchai Chongcheawchamnan; Monai Krairiksh (My University, 2008)
In this paper, a simple transmission line model for an edge-coupled patch antenna is presented. The coupled section is modeled with a lump network which represents the mutual admittance between patches and from patch to ground. Theoretical analysis of two edge-coupled patch antenna models are compared by simulation and experiment in antennas designed to operate at the 2 GHz band. The proposed model predicts the return loss of the antenna accurately.
Keywords: Patch antenna; Return loss; Line (geometry); Antenna Design and Analysis